Corporate Transformation Towards Sustainability: The Case of the Indonesian Pulp and Papers Industry - Abra P. G. Talattov; M. Ridzki Wibowo; Mei Kallman (The Indonesian Forestry Certification Cooperation, 2021)
This paper explores the process of sustainability transformation on pulp and paper industry in Indonesia, including the factors driving sustainability, challenges of integrating sustainability, and current best practices in the industry. We used a qualitative research methodology, interview and examine sustainability reports of APP and APRIL, two leading pulp and paper companies in Indonesia. We find a total of 4 drivers and 2 main challenges in the transformation process. The four drivers are: risk and risk reduction, expectation of key stakeholders, i.e., market, consumers, investors, society; competitive advantage, and top management. The two main challenges are the initial investment required and the lack of competence to manage the alleged paradox of improving environmental, social, and economic goals at the same time. However, despite the challenges presented, we find that the transformational process has resulted in a positive impact for the companies’ triple bottom line.